KLASIFIKASI KIMONO SEBAGAI BUSANA ADAT JEPANG - Mila Fiska Indriana; Iffana Nafisa Saraswati; Amin Sulistiyowati (Akademi Seni dan Desain Indonesia Surakarta, 2024)
This journal uses qualitative research methods through document or text studies. It is a study that focuses on the analysis or interpretation of written material based on the context. Materials can be in the form of published notes, books, texts, newspapers, magazines, articles and the like. The data used as a reference for this journal is taken from online journals and digital books, which have previously been reviewed by the author and then summarized and set forth in written form with the title Classification of Kimono as Japanese Traditional Clothing. Japan is included in one of the developed countries, Japan as a country that still adheres to customs and culture is the main attraction, one of which is clothing. Almost everyone knows the traditional Japanese dress, namely the kimono. Clothing with various motifs and colors is well known throughout the world because it has become the identity of the country. Traditional Japanese kimono clothing is no longer monotonous because it has received several technological touches so that it looks more modern and can compete in the market.